LTCC Ka-band bandpass filters with half-wavelength inverted-L stubs. Issue 12 (December 2015) - Chin, Kuo-Sheng; Huang, Chun-Wei; Chang, Chih-Chun; Chou, Kuang-Tsung; Kuo, Hao-Che
Abstract: This study designed a compact Ka-band open-circuited stub bandpass filter by using the low-temperature cofired ceramic technology. A novel inverted-L stub resonator was developed in the design of 37-GHz third-order bandpass filters. When the operating frequency is high, the proposed structure is highly useful for maintaining extremely low impedance levels in stubs to prevent distorting the filter performance. The design concept was validated by measuring a fabricated filter; the filter demonstrated an insertion loss of 1.9 dB, return loss of 18 dB, and bandwidth of 23.5%.